2023
DOI: 10.1021/acs.jctc.2c01036
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Spin–Orbit Coupling by Relativistic Mixed-Reference Spin-Flip-TDDFT

Abstract: Relativistic mixed-reference spin-flip (MRSF)-TDDFT is developed considering the spin–orbit coupling (SOC) within the mean-field approximation. The resulting SOC-MRSF faithfully reproduces the experiments with very high accuracy, which is also consistent with the values by four-component (4c) relativistic CASSCF and 4c-CASPT2 in the spin–orbit-energy splitting calculations of the C, Si, and Ge atoms. Even for the fifth-row element Sn, the SOC-MRSF yielded accurate splittings (∼ 3 % error). In the SOC calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…To alleviate the situation, recently, some of us have explored the optimization of XC functionals for MRSF, 19 where it was shown that significant prediction accuracy improvements can be achieved with the help of a "double tuning" idea. Rather than utilizing the same XC functionals during the entire computational process, the use of adaptive XC functionals was attempted for the reference Kohn−Sham (KS) DFT and the response part of calculations, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate the situation, recently, some of us have explored the optimization of XC functionals for MRSF, 19 where it was shown that significant prediction accuracy improvements can be achieved with the help of a "double tuning" idea. Rather than utilizing the same XC functionals during the entire computational process, the use of adaptive XC functionals was attempted for the reference Kohn−Sham (KS) DFT and the response part of calculations, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 The "double tuning" idea in the framework of the Coulomb-attenuated method (CAM) functional yielded two new XC functionals of the doubly tuned Coulomb-attenuated method, (DTCAM)-VEE and DTCAM-AEE, for vertical excitation energies (VEEs). 19 T h i s c o n t e n t i s In the current paper, further investigations shall be performed toward consistent predictions of both core/valence ionization potentials (cIPs/vIPs) and VEEs in the search for universally useful XC functionals for MRSF. As X-ray light sources with an intense and coherent pulse like X-ray freeelectron lasers 21 are becoming available, significant attention has been directed to X-ray spectroscopy, 22 leading to the timeresolved (TR) variants of X-ray absorption spectroscopy (XAS), photoelectron spectroscopy (XPS), etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Therefore, after its initial introductions, the MRSF-TDDFT 27,29 has proven to be a promising quantum theory for general use, overcoming the major issues of existing theories. In a series of studies, [30][31][32][33][34][35][36][37][38][39][40] it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs) 35,36 enabling reliable nonadiabatic molecular dynamics (NAMD) simulations, 39,[41][42][43][44][45][46] accurate spin-orbit couplings (SOC) 47 and very accurate X-ray absorption predictions. 48 This method has also been successfully used in designing highly performing optoelectronic materials.…”
Section: Introductionsmentioning
confidence: 99%
“…Therefore, after its initial introductions, the MRSF-TDDFT , has proven to be a promising quantum theory for general use, overcoming the major issues of existing theories. In a series of studies, it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs) , enabling reliable nonadiabatic molecular dynamics (NAMD) simulations, , accurate spin–orbit couplings (SOC), and very accurate X-ray absorption predictions . This method has also been successfully used in designing highly performing optoelectronic materials. , The MRSF-TDDFT has finally been released publicly by GAMESS (July 31, 2022 R1 Public Release Version) …”
Section: Introductionsmentioning
confidence: 99%